A Digital Platform Ecosystem for Circular Economy Implementation: Design and Development of the Toraja Coffee Cascara Value Chain Management System - Belo Tarran; Eddy Soeryanto Soegoto; Farmonov O'ktam Ne'matovich (International Journal of Research and Applied Technology (INJURATECH), 2026)
Toraja coffee pulp, typically wasted in post-harvest processing, presents untapped economic potential as a premium cascara tea product. This study develops a comprehensive digital business framework to transform this agricultural byproduct into a sustainable commodity. Employing a descriptive qualitative strategy grounded in Design Science Research Methodology (DSRM), the research constructed novel artifacts addressing practical challenges in cascara commercialization: a digital platform eliminating supply chain intermediaries, a Triple Layer Business Model Canvas balancing economic, environmental, and social dimensions, and a mobile-based farmer education system. The DSRM approach emphasized iterative development of these models and systems through stakeholder engagement, including in-depth interviews with farmers and processors, focus group discussions with cooperatives, and pilot implementation with selected farmer groups. Qualitative data were analyzed using thematic coding and content analysis. Results demonstrate significant synergy between digital platform technology and circular business models, with the digital platform reducing supply chain inefficiencies, improving farmer profit margins, and enhancing transparency, while structured farmer education standardizes coffee pulp quality according to international hygiene criteria. These findings reveal that integrating digital innovation, circular economy principles, and targeted farmer education generates substantial value-added benefits across economic, environmental, and social dimensions. The study concludes that this integrated approach, developed through rigorous design science methodology, creates viable pathways for establishing a sustainable cascara tea ecosystem in Toraja, simultaneously maximizing economic opportunity for farmers while minimizing environmental impact.